Complications and prognosis of patients undergoing apical or septal right ventricular pacing. Issue 1 (9th February 2019) - Spath, Nick B; Wang, Kelvin; Venkatasumbramanian, Sowmya; Fersia, Omar; Newby, David E; Lang, Chris CE; Grubb, Neil R; Dweck, Marc R
Abstract : Objectives: Optimal right ventricular lead placement remains controversial. Large studies investigating the safety and long-term prognosis of apical and septal right ventricular lead placement have been lacking. Methods: Consecutive patients undergoing pacemaker insertion for high-degree atrioventricular block at Edinburgh Heart Centre were investigated. Periprocedural 30-day complications were defined (infection/bleeding/pneumothorax/tamponade/lead displacement). Long-term clinical outcomes were obtained from the General Register of Scotland and electronic medical records. The primary endpoint was a composite of all-cause mortality, new heart failure, hospitalisation for a major cardiovascular event, as per the CA rdiac RE synchronization in H eart F ailure trial. Secondary endpoints were all-cause mortality, new heart failure and their composite. Results: 820 patients were included, 204 (25%) paced from the septum and 616 (75%) from the apex. All baseline variables were similar with the exception of age (septal: 73.2±1.1 vs apical: 76.9±0.5 years, p<0.001). Procedure duration (58±23 vs 55±25 min, p=0.3), complication rates (18 (8.8) vs 46 (7.5)%, p=0.5) and postimplant QRS duration (152 (23) vs 154 (27) ms, p=0.4) were similar. After 1041 days (IQR 564), 278 patients met the primary endpoint, with no difference between the septal and apical groups in unadjusted (HR 0.86 (95% CIs 0.64 to 1.15)) or multivariable analysis correcting for age, gender and comorbidity (HR 0.97 (95% CI 0.72 to 1.30)). Similarly, no differences were observed in the secondary endpoints. Conclusions: This large real-world cohort of patients undergoing right ventricular lead placement in the septum or apex demonstrated no difference in procedural complications nor long-term clinical outcomes. Both pacing strategies appear reasonable in routine practice.